Digital transponder design - Kothuri Dileep Chakravarthy. (2008)
The objective of the project is to design a ground station demodulator for a Low Earth Orbit satellite that is intended to be launched in 2006. The BPSK modulated data from the satellite is expected to arrive with a frequency of 70MHz (+/-50KHz), where the intended data rate is 500KHz. This data comprises of the telemetric signals to be transferred from the satellite to the ground station.